Decolonising cultural policy : the cultural and linguistic rights of the Sámi in Finland - Valoma, Laura (Frontiers, 2024)
In this article, the writer considers the current state of the cultural and linguistic rights of the Sámi, how they are supported by cultural policy and how decolonising cultural policy could contribute to the ongoing struggles of realising the self-determination and cultural rights of the Sámi. The article stipulates that concrete steps need to be taken for decolonising cultural policy in Finland specifically concerning the cultural and human rights of the Sámi. Cultural policy should be based on cultural rights, thus introducing decolonial practices in support of the Sámi culture and languages and into the culture policy and funding is imperative. The article suggests creating decolonial practices of research and policymaking rooted in intersectional and participatory methods that recognise the many forms of discrimination, not only the current-day colonialism or the effects of assimilation but also the intersections of an indigenous identity with other forms of discrimination. Furthermore, contributing to decolonisation should include research on the effects of colonisation on cultural rights, cultural policy and the distribution of funds for promoting the Sámi culture and languages in the Sámi communities and Finland.
Keywords: kulttuuripolitiikka; sivistykselliset ja kulttuuriset oikeudet; dekolonisaatio; kolonialismi; saamelaiset